Oracle Blockchain Quick Start Guide : a Practical Approach to Implementing Blockchain in Your Enterprise. - Acharya, Vivek (Packt Publishing, Limited, 2019)
Blockchain empowers enterprises to scale out in a unique way, allowing them to build and manage blockchain business networks. This book offers an exploration of distributed ledger technology, blockchain, and Hyperledger fabric along with blockchain-as-a-service (BaaS).